2002
DOI: 10.1070/rd2002v007n02abeh000204
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this paper we consider cases of existence of invariant measure, additional first integrals, and Poisson structure in a problem of rigid body's rolling without sliding on plane and sphere. The problem of rigid body's motion on plane was studied by S. A. Chaplygin, P. Appel, D. Korteweg. They showed that the equations of motion are reduced to a secondorder linear differential equation in the case when the surface of dynamically symmetric body is a surface of revolution. These results were partially generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
15

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 7 publications
0
62
0
15
Order By: Relevance
“…Thus, we have shown that the framework suggested by Borisov, Mamaev and Kilin [7,8] can be improved along the lines discussed, namely, that those reduced systems need no rescaling to become Hamiltonian with respect to a Poisson structure of rank two, and that the domain of definition of the Poisson structures introduced therein can be extended, including even the set of singular equilibria of the reduced systems. A natural question is whether a similar approach could be used in other non-holonomic systems, maybe of higher dimension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we have shown that the framework suggested by Borisov, Mamaev and Kilin [7,8] can be improved along the lines discussed, namely, that those reduced systems need no rescaling to become Hamiltonian with respect to a Poisson structure of rank two, and that the domain of definition of the Poisson structures introduced therein can be extended, including even the set of singular equilibria of the reduced systems. A natural question is whether a similar approach could be used in other non-holonomic systems, maybe of higher dimension.…”
Section: Discussionmentioning
confidence: 99%
“…This problem has been treated as well, e.g., in [4,7,20,33,35]. Consider a sphere of mass m and radius r with its center of mass at a distance α (0 < α < r) from its geometric center.…”
Section: Routh's Spherementioning
confidence: 99%
See 2 more Smart Citations
“…ªÔÕÑÓËâ ËÊÖÚÇÐËâ àÕËØ ÔËÔÕÇÏ ÃÑÅÂÕ AEÓÂÏÂÕËÚÇÔÍËÏË ÏÑÏÇÐÕÂÏË, Ä ÕÑÏ ÚËÔÎÇ ÑÛËÃÍÂÏË, ÍÑÕÑÓÞÇ ÔÑÄÇÓÛÂÎËÔß ÄËAEÐÞÏË ËÔÔÎÇ-AEÑÄÂÕÇÎâÏË Ë ÎËÛß ÊÂÕÇÏ ËÔÒÓÂÄÎâÎËÔß Ä ØÑAEÇ ÃÑÎÇÇ ÂÍÍÖÓÂÕÐÑÅÑ ÂÐÂÎËÊÂ. ªÇÓÂÓØËâ ÕËÒÑÄ ÒÑÄÇAEÇÐËâ ÐÇÅÑÎÑ-ÐÑÏÐÞØ ÔËÔÕÇÏ [9,10] …”
unclassified